Deep in the Sahara - Cunnane, Kelly (Schwartz & Wade Books, 2013)
In Mauritania, West Africa, an Arab girl who wants to wear a malafa, the veiled dress worn by her mother and older sister, learns that the garment represents beauty, mystery, tradition, belonging, and faith.